Information System Strategy Planning Using Enterprise Architecture Planning in College Libraries - Arie Gunawan; Agus Rahayu; Lili Adi Wibowo (Institute of Computer Science (IOCS), 2021)
The library of the National University of Jakarta currently records transactions manually, which makes the librarian's performance inefficient. Here, the researcher is trying to create information system planning that covers all perspectives of the organization and business with the help of the enterprise architecture planning (EAP) technique using the Zachman framework. The EAP model is limited to the main business area, the library sector, which creates the main activities and support activities according to Porter's value chain. Based on the business processes implemented by the library, EAP can show the design for an integrated architecture within the library information system, which includes business architecture, data architecture, application architecture, infrastructure architecture, and implementation plans to bring about changes for the better.